Refractive Error and Eye Health: An Umbrella Review of Meta-Analyses - Wang, Yin-hao; Huang, Chen; Tseng, Yu-lin; Zhong, Jing; Li, Xue-min (Frontiers in Medicine, 2021)
Purpose: To explore the associations between refractive errors and multiple eye health outcomes. Methods: This is an umbrella review based on systematic reviews with meta-analyses. In our study, refractive errors included myopia, hyperopia, astigmatism, and anisometropia. We reconducted the meta-analyses whose primary data were available in sufficient detail by random effect model. Heterogeneity was assessed by I2. The main outcomes included myopic macular degeneration (MMD), retinal detachment (RD), cataract, open-angle glaucoma (OAG), strabismus, age-related macular degeneration (AMD), and diabetic retinopathy (DR). Results: Myopia was associated with increased risk of MMD (relative risk=102.11, 95% confidence interval 52.6–198.22), RD (3.45, 1.08–11.00), nuclear cataract (2.15, 1.53–3.03), posterior subcapsular (PSC) cataract (1.74, 1.41–2.15), OAG (1.95, 1.74–2.19), exotropia (5.23, 2.26–12.09), but decreased risk of DR (0.83, 0.66–1.04), and early AMD (0.80, 0.67–0.94). From mild to high myopia, the association strengthened for MMD, RD, nuclear cataract, PSC cataract, OAG, and DR. Hyperopia was associated with increased risk of early AMD (1.09, 1.01¬–1.18) and esotropia (22.94, 10.20–51.62). Astigmatism and anisometropia were associated with increased risk of both exotropia and esotropia. Conclusions: Myopia, especially high myopia, demonstrated the highest risk for eye health outcomes, including MMD, RD, OAG, nuclear and PSC cataract, and exotropia. However, myopia was associated with lower risk of early AMD and DR. Individuals with hyperopia are more likely to suffer early AMD and esotropia. Astigmatism and anisometropia predispose to strabismus. More researches studying the mechanism of the associations are needed.